An Open-Design Warehouse Mobile Robot - Barros, Rhaian; Silva Filho, Jorge; S. Neto, João; Nascimento, Tiago (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
With the advancement of Warehouses automation, robots are increasingly a desirable tool. The creation of the Robotic Mobile Fulfillment System after the market implementation of the American Kiva Robotic Systems and the Chinese Cainiao Robots, and the increasing need for this technology in a national perspective, motivated the proposal of this work. The objective of this work is to present the starting step for the design of a Brazilian Warehouse Mobile Robot. Here we provide an overview of a possible mechanical, electrical and computational configuration, as well as provide the simulation environment based on ROS for a warehouse environment. Most of the material can be found on online market and can also be the building block for any national robot development, independent of the country.